Recent Advancement In Nanocarrier Systems For Cancer Targeting - Teron, Charlisar; Choudhury, Ananta; Hoque, Nurjamal (Asian Journal of Pharmaceutical Research and Development, 2024)
Cancer is a disease that has a complicated pathological process. Current chemotherapy has issues such as lack of selectivity, cytotoxicity, generation of multi-drug resistance, and the formation of stem-like cells. The novel treatment modalities enabled by nanomaterial characteristics have expanded their reach in cancer therapy beyond traditional medication delivery. Nanotechnology has been actively researched and used in cancer treatment because nanoparticles can serve as an effective medication delivery mechanism. Nanoparticle-based drug delivery provides distinct benefits over traditional drug administration, including greater stability and biocompatibility, increased permeability and retention effect, and precision targeting. There are numerous major categories of nanomaterials utilized in cancer treatment. These nanomaterials, which target cancer cells, the tumor microenvironment, and the immune system, have been modified for a variety of cancer treatments in order to overcome toxicity and lack of selectivity, as well as to improve drug capacity and bioavailability. Furthermore, nanoparticle-based drug delivery systems have been found to help overcome cancer-related treatment resistance. In cancer therapy, nanoparticles can be used to encapsulate active pharmacological substances and deliver them to the tumor location more efficiently. This overview lists the several types of nanoparticles that have been tested in clinical trials for cancer therapy. Furthermore, the most recent advancements in the use of nanoparticles in cancer therapy are emphasized.The literature for this study was compiled using databases such as PubMed, Google Scholar, and ScienceDirect on nanoparticles in the treatment of cancer have been collected. The present article focuses on nanotechnology advancements, specifically nanocarriers for anticancer medication delivery. It covers nanoparticles, polymeric micelles, dendrimers, hydrogels system and finally the future prospects of the nanocarrier.